Perbedaan Kualitas Semen Segar Sapi Eksotik pada Musim yang Berbeda di Balai Inseminasi Buatan NTB : Differences in Fresh Semen Quality from Exotic Cattle in Different Seasons at the NTB Artificial Insemination Center - Rizqi, Ma'wa; Munandar, Imam (Fakultas Ilmu dan Teknologi Hayati Universitas Teknologi Sumbawa, 2025)
This study aims to determine the differences in the quality of fresh semen from exotic cows during different seasons at the Regional Insemination Center of West Nusa Tenggara Province. The research was conducted at the Regional Artificial Insemination Center of West Nusa Tenggara Province from February 10 to 20, 2025. The variables examined included semen volume, pH, sperm motility, and sperm concentration. Data analysis involved comparing paired T-tests using Tools Excel. Based on the research results, different seasons showed variations in semen quality. The best values were observed during the dry season, with an average semen volume of 4.84 ± 2.02 ml and a pH of 7.01 ± 5.24. In contrast, during the rainy season, the average sperm motility was 66.55 ± 9.58%, and the sperm concentration was 1569.95 ± 430.36 x 10?/ml. The quality of fresh semen from exotic bulls at BIBD was influenced by seasonal differences, particularly in terms of semen volume.